A review on the relationship between social media usage, social media sharing, and depressive symptoms among university students - Nur Amni Aqilah Mohamed Izam; Jamilah Hanum Abdul Khaiyom; Junita Nawawi (Penerbit Universiti Kebangsaan Malaysia, 2019)
University students were found to have high depressive symptoms, and one of the contributing factors may be social media usage. Multiple studies have found mixed results regarding the relationship between social media usage and depressive symptoms. Some studies found a significant negative relationship between social media usage and depressive symptoms, while several others found an indirect significant relationship or no relationship between these two variables. The difference may be due to other factors such as individuals sharing their positive and negative experiences on social media. Sharing positive experience was found to reduce negative affect (e.g. depression) while sharing negative experience was found to increase negative affect. Therefore, this literature review aims to review these topics, specifically, (1) the relationship between social media usage and depressive symptoms, (2) the relationship between social sharing and depressive symptoms, and (3) to integrate a possible explanation related to the relationship between social media usage, social sharing, and depressive symptoms.